Climate precursors of multidecadal drought variability in the western United States - Hidalgo León, Hugo G. (2004)
Low-frequency (periodicities lower than 20 years) hydrologic variability in the western United States over the past 500 years is studied using available tree-ring reconstructions of Palmer Drought Severity Index (PDSI), streamflow, and climate indices. Leading rotated principal component (RPC) scores of a gridded tree-ring reconstruction of the PDSI from 1525 to 1975 are significantly correlated with indices representing large-scale climate variations from the Pacific and Atlantic Oceans. RPC1 (31%) is related to the influence of North Pacific sea surface temperature (SST) variations, indexed by the Pacific Decadal Oscillation (PDO). RPC2 (24%) is apparently related to North Atlantic SST variations, indexed by the Atlantic Multidecadal Oscillation (AMO). RPC3 (19%) is moderately correlated with a smoothed version of the Southern Oscillation Index. Consistent with recent studies of instrumental data, RPC1 (PDO) and RPC2 (AMO) explain a large part of the multidecadal hydrologic variability of the interior western United States. Western U.S. PDSI variability exhibits significant pentadecadal (and longer) oscillations in the epochs from circa 1525 to 1650 and 1850 to 1975, while bidecadal oscillations are prevalent in the middle epoch from circa 1650 to 1850. The changes in spectral characteristics of western U.S. PDSI were related to similar changes in the PDO (and therefore in RPC1). In contrast, RPC2 had a regular periodicity of 51 years for the past ∼500 years. This regularity is intriguing, and although RPC2 was primarily related to the AMO in this study, the influence from Pacific climate cannot be discarded.